2022
DOI: 10.18502/ijaai.v21i1.8609
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the MicroRNA Expression of IL-35 and IL-37 in Helicobacter pylori-infected Patients with Gastritis and Gastric Ulcer

Abstract: Interleukin (IL)-35 and IL-37 are two anti-inflammatory cytokines. IL-35 inhibits the development of T-effector cells such as Th1, and Th17; while increasing regulatory T cells (Tregs). IL-37 causes the suppression of inflammatory cytokines. Regarding the positive impact of Helicobacter pylori (H. pylori) infection on inflammation and considering the anti-inflammatory effects of IL-35 and IL-37, this study aimed to evaluate the expression of these two cytokines in H. pylori-infected patients with gastrointesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…As a newly discovered inflammatory factor, the anti-inflammatory effect of IL-37 is gradually being investigated. Several studies demonstrated that IL-37 has potential protective effects against inflammatory diseases, including colitis and gastritis ( 36-38 ). Furthermore, it was also reported that IL-37 improved the function of plasma dendritic cells in patients with acute coronary syndrome ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a newly discovered inflammatory factor, the anti-inflammatory effect of IL-37 is gradually being investigated. Several studies demonstrated that IL-37 has potential protective effects against inflammatory diseases, including colitis and gastritis ( 36-38 ). Furthermore, it was also reported that IL-37 improved the function of plasma dendritic cells in patients with acute coronary syndrome ( 11 ).…”
Section: Discussionmentioning
confidence: 99%